DNA-Free Genome Editing: Past, Present and Future - Metje-Sprink, Janina; Menz, Jochen; Modrzejewski, Dominik; Sprink, Thorben (Frontiers in Plant Science, 2019)
Genome Editing using engineered endonuclease (GEEN) systems has rapidly taken over the field of plant science and plant breeding. So far, Genome Editing techniques have been applied in more than fifty different model plants and crops including main crops like rice, maize or wheat as well as economically less important crops like strawberry, peanut or cucumber. Mainly, these techniques have been used for basic research as proof-of-concept or to investigate gene functions. However, several market-oriented applications were developed including improved agronomic characteristics, improved food and feed quality, increased tolerance to abiotic and biotic stress and herbicide tolerance. These technologies are evolving at a tearing pace and especially the field of CRISPR Genome Editing is advancing incredibly fast. CRISPR-Systems derived from a multitude of bacterial species are being used for targeted Gene Editing and many modifications have already been applied to the existing CRISPR-Systems such as (i) alter their protospacer adjacent motif (ii) increase their specificity (iii) alter their ability to cut DNA and (iv) fuse them with additional proteins. Besides, the classical transformation system using Agrobacteria tumefaciens or Rhizobium rhizogenes, other transformation technologies have become available and additional methods are on its way to the plant sector. Some of them are solely using proteins or protein-RNA complexes for the transformation, making it possible to alter the genome without the use of recombinant DNA. Due to this it is impossible that foreign DNA is incorporated into the host genome. In this perspective paper we will give an overview on the recent developments and techniques in the field of DNA-free Genome Editing, its advantages and pitfalls and give a perspective on which technologies might be available in the future for targeted Genome Editing in plants. Furthermore, we will discuss these techniques in the light of existing-- and potential future regulations.